Childhood multiple sclerosis is associated with reduced brain volumes at first clinical presentation and brain growth failure. (June 2019) - Bartels, Frederik; Nobis, Katharina; Cooper, Graham; Wendel, Eva; Cleaveland, Robert; Bajer-Kornek, Barbara; Blaschek, Astrid; Schimmel, Mareike; Blankenburg, Markus; Baumann, Matthias; Karenfort, Michael; Finke, Carsten; et al.
Background: Paediatric multiple sclerosis (pedMS) patients at a single site were shown to have reduced brain volumes and failure of age-expected brain growth compared to healthy controls. However, the precise time of onset of brain volume loss remains unclear. Objective: To longitudinally study brain volumes in a multi-centre European cohort at first presentation and after 2 years. Methods: Brain volumes of high-resolution magnetic resonance imaging (MRI) data from 37 pedMS patients at first presentation prior to steroid therapy and at 2-year follow-up ( n = 21) were compared to matched longitudinal MRI data from the NIH Paediatric MRI Data Repository. Results: Patients showed significantly reduced whole brain, grey and white matter and increased ventricular volumes at initial presentation and at follow-up compared to controls. Over 2 years, patients exhibited significant reduction of whole brain and white matter volumes, accompanied by increased ventricular volume. Brain volume loss at follow-up correlated with a higher number of infratentorial lesions, relapses and an increased Expanded Disability Status Scale (EDSS) score. Conclusions: In pedMS patients, brain volume loss is present already at first clinical presentation and accelerated over 2 years. Increased disease activity is associated with more severe brain volume loss. MRI brain volume change might serve as an outcome parameter in future prospective pedMS studies.